Advanced neural activity mapping in brain organoids via field potential imaging with ultra-high-density CMOS microelectrode arrays - Yokoi, Remi; Matsuda, Naoki; Ishibashi, Yuto; Suzuki, Ikuro (Frontiers in Neuroscience, 2025)
IntroductionHuman iPSC-derived brain organoids and assembloids have emerged as promising in vitro models for recapitulating human brain development, neurological disorders, and drug responses. However, detailed analysis of their electrophysiological properties requires advanced measurement techniques.MethodsHere, we present an analytical approach using ultra-high-density (UHD) CMOS microelectrode arrays (MEAs) with 236,880 electrodes across a 32.45 mm2 sensing area, enabling large-scale field potential imaging (FPI) of brain organoids.ResultsNeuronal activity was recorded from over 46,000 electrodes, allowing single-cell spike detection and network connectivity analysis. In midbrain organoids, L-DOPA administration elicited both excitatory and inhibitory responses, with a dose-dependent shift toward network enhancement. Leveraging the spatiotemporal resolution of the UHD-CMOSMEA, we introduced two novel endpoints: propagation velocity and propagation area. In cortical organoids, picrotoxin increased propagation velocity, while MK-801 reduced propagation area. FPI also enabled frequency-domain analyses, revealing region-specific activity, including distinct gamma-band patterns. In midbrain–striatal assembloids, 4-aminopyridine enhanced interorganoid connectivity.ConclusionThis single-cell-resolved, large-scale recording approach using UHD-CMOS MEAs enables detailed analysis of network connectivity, propagation dynamics, and frequency features. It provides a powerful platform for studying brain organoids and assembloids, with strong potential for drug discovery and disease modeling in human neuroscience.